Analysis of Hydroquinone in Face Whitening Cream Circulating in Semarang City Using UV-Vis Spectrophotometry Method - SIRAIT, Ernessa Indah Rotua; Widhihastuti, Endah (Universitas Negeri Semarang, 2023)
The Food and Drug Supervisory Agency of the Republic of Indonesia issued a regulation that hydroquinone with levels above two percent is a class of strong drugs that can only be given with a doctor's prescription. However, reality shows that many manufacturers misuse hydroquinone as an over-the-counter cream with a content of more than 2%. This study aims to determine the validity of the UV-Vis spectrophotometric method for hydroquinone analysis, to test the hydroquinone content and levels in whitening creams sold in Semarang, and to ascertain whether these levels comply with BPOM regulations. A total of 10 samples of facial whitening creams obtained from cosmetic shops located in North Semarang, East Semarang, West Semarang, Central Semarang and South Semarang were subjected to qualitative tests and quantitative tests. Method validation test was carried out to ensure the validity of the results obtained. The validation parameters used are linearity, LOD and LOQ, precision and accuracy. The results showed that the UV-Vis spectrophotometric method was valid for hydroquinone analysis in samples of facial whitening cream for all tested parameters. The linear regression equation obtained is y=0,0132x+0,0655 with r=0,9986 and R2=0,9973; the maximum wavelength is 294 nm, high precision with %RSD obtained by 0,84%, the LOD and LOQ values ​​were 2,5 µg/ml and 8,3 µg/ml, and the accuracy value was 100,211%. Then a qualitative test was carried out on each sample of facial whitening cream by comparing the spectrum between each sample and the standard spectrum of hydroquinone to identify the presence or absence of hydroquinone. The results of samples A, G, H, and J were not identified as containing hydroquinone, while samples B, C, D, E, F, and I were identified to contain hydroquinone. The quantitative test was carried out by determining the levels of hydroquinone in a sample of facial whitening cream using a linear regression equation. The hydroquinone content in the sample A, G, H, and J could not be determined because they were not detected by the spectrophotometer used. Hydroquinone levels in creams B, C, D, E, F, and I each have a value of 0.84%; 4.77%; 0.74%; 2.27%; 4.75%; and 1.39%.